Analisis Pengaruh Pengadopsian IFRS dan Tata Kelola Perusahaan Terhadap Manajemen Laba pada Perusahaan di BEI - Agustina, Agustina; Sumantri, Sumantri (Faculty of Economics, Universitas Internasional Batam, 2018)
This reseacrh is conducted to determine the impact of IFRS adoption and good corporate governance on earnings management in companies listed in Indonesia Stock Exchange. Variables used in this reseacrh are IFRS adoption, board director independence, boarddirector size, audit committee Independence, audit quality, ownership concentration, managerial ownership, institutional ownership, company size, sales growth, asset turnover, cash flow from operation, and leverage. This study used 242 companies listed on IDX in the period 2009-2014 as the sample. The sample was selected using purposive sampling method. Data sources in this study were obtained from the annual report of listed companies on IDX. The data will be tested with multiple linear regresion using Statistical Package for the Social Sciences (SPSS) and E-Views. The results of this study indicate that ownership concentration,managerial ownership, institutional ownership, company size, sales growth show a positive impact on earning management significantly. Board director size, audit quality, cash flow from operation, and leverage show a negative impact on earning management significantly. IFRS adoption, board director independence, audit committee Independence, and asset turnover are not able to affect earning management activity significantly.